Analisis Peningkatan Kinerja Aparatur Sipil Negara Melalui Pengembangan Kompetensi, Disiplin, Dan Etos Kerja Pada Sekretariat DPRD Kabupaten Tulungagung - Agustina, Ratna; Daroini, Ahsin (Universitas Islam Kadiri, 2025)
The Secretariat of the Tulungagung Regency DPRD as a regional apparatus organization that is at the forefront in serving the community, requires quality human resources, professional, innovative, creative and responsive to community aspirations and responsible in handling various problems. This study aims to: (1) To determine and analyze the influence of organizational development on improving the performance of the State Civil Apparatus. (2) To determine and analyze the influence of discipline on improving the performance of the State Civil Apparatus. (3) To determine and analyze the influence of work ethic on improving the performance of the State Civil Apparatus. (4) To determine and analyze the influence of competency development, discipline, and work ethic on improving the performance of the State Civil Apparatus. (5) To determine and analyze the influence of competency development, discipline, and work ethic variables that have the most dominant influence on improving the performance of the State Civil Apparatus. This study uses a quantitative analysis method, namely analysis of data that has been scored according to the measurement scale that has been determined using statistical formulas. The analysis used is for data in the form of numbers. While the data analysis method uses: (1) Descriptive Statistical Analysis, (2) Verification Analysis, (3) Classical Assumption Test, (4) Multiple Regression Analysis, (5) Hypothesis Testing, and (6) Determination Coefficient Analysis. The results of the study show that: (1) Competency development has a significant influence on Improving ASN Performance at the Tulungagung Regency DPRD Secretariat. (2) Discipline has a significant influence on Improving ASN Performance at the Tulungagung Regency DPRD Secretariat. (3) Work ethic has a significant influence on Improving ASN Performance at the Tulungagung Regency DPRD Secretariat. (4) Competency development, discipline, and work ethic have a significant influence on Improving ASN Performance at the Tulungagung Regency DPRD Secretariat. (5) Discipline has the most dominant influence on improving ASN performance at the Tulungagung Regency DPRD Secretariat.